2014
DOI: 10.1016/j.pain.2014.09.034
|View full text |Cite
|
Sign up to set email alerts
|

National study of discontinuation of long-term opioid therapy among veterans

Abstract: Introduction Veterans have high rates of chronic pain and long-term opioid therapy (LTOT). Understanding predictors of discontinuation from LTOT will clarify the risks for prolonged opioid use and dependence among this population. Methods All veterans with at least 90 days of opioid use within a 180 day period were identified using national Veteran's Health Affairs (VHA) data between 2009 and 2011. Discontinuation was defined as 6 months with no opioid prescriptions. We utilized Cox proportional hazards anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 30 publications
5
35
0
1
Order By: Relevance
“…This is in line with US studies of discontinuation rates among chronic opioid users, which have found that the majority of patients who received at least 90 days of continuous opioid therapy over a six-month period remained on opioid therapy years later. 25,26 We found that an increasing proportion of BC residents are becoming long-term opioid users. This is driven by a discontinuation rate among users that is lower than the incidence of new users: for every 19 new long-term users in a given year, 16 existing long-term users will discontinue therapy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is in line with US studies of discontinuation rates among chronic opioid users, which have found that the majority of patients who received at least 90 days of continuous opioid therapy over a six-month period remained on opioid therapy years later. 25,26 We found that an increasing proportion of BC residents are becoming long-term opioid users. This is driven by a discontinuation rate among users that is lower than the incidence of new users: for every 19 new long-term users in a given year, 16 existing long-term users will discontinue therapy.…”
Section: Discussionmentioning
confidence: 85%
“…Median [interquartile range, IQR] daily dose during the episode of long-term use was 4 [3-5] ME for occasional users, 8 [5][6][7][8][9][10][11]] ME for regular users, 17 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] ME for chronic users and 79 [33-197] ME for every-day users.…”
Section: Long-term Opioid Use For Non-cancer Pain In Bcmentioning
confidence: 99%
“…But deprescribing is difficult for most GPs with 89%, in an Australian survey, reporting never or only “ occasionally” terminating opioids even when faced with aberrant opioid behaviors . In a large US survey one year after the commencement of long‐term opioid analgesia, only 7.5% patients had discontinued them and only 20% had done so when followed for up to 3.5 years . The potential for adverse effects in continued prescribing is highlighted in another US study which showed that duration of opioid analgesia prescribing is strongly associated with risk of opioid use disorders .…”
Section: Discussionmentioning
confidence: 99%
“…CNCP was defined as having at least one diagnosis for one of the following five major conditions: arthritis, back pain, neck pain, neuropathic pain or headache/migraine from 1 October 2008 to 30 September 2015 . Among those with CNCP, Veterans were further required to receive at least a 90 days’ supply of non‐parenteral opioids without a 30‐day or more gap in supply within two consecutive 180‐day periods . The first period served as the baseline period, and the second was used to determine if the Veteran escalated or maintained their dose.…”
Section: Methodsmentioning
confidence: 99%